SEED GERMINATION AND SEEDLING EMERGENCE OF Sorghum alepenseL IN RELATION TO THE POSITION OF DEVELOPMENT SEEDS ON INFLORESENCE AND TIME OF SEED MATURITY - A . M . Sultan (Mesopotamia Journal of Agriculture)
Pots experiment was carried out at the College of Agric & Forestry , Mosul University in summer growing season of 2003 to determine the percentage of germination and seedling emergence for Sorghum halepense L seed which developed from different positions on infloresence of mother plant in relating to different time of seed maturity . Data was subjected to the convertional analysis of complete Randomized Design ( C.R.D ) as a factorial experiment . Result indicated that the germination percentage had significantly reduced 60.1 % when the seeds matured at october comparing with the seed maturity at july . On other hand , Seed that had been taken from lower part of infloresence had less variability or less percentage of germination than those taken from upper part of infloresence . Dry weight of emergering seedling also reduced up to 35.7 % when it was collected at september than at August , while 18.6 had reduced in dry weight from the seeds had matured from the lower part of mother infloresence .